Sustainable Export Innovation Behavior of Firms Under Fiscal Incentive - Feng, Chen; Shi, Beibei; Yan, Hong; Yang, Siying; Bai, Caiquan (Frontiers in Psychology, 2021)
The fiscal imbalance between the central and local governments under fiscal centralization may motivate local governments to pass tax burdens on the firms. The causal identification of the tax system reform and firms’ sustainable export innovation behavior is of great significance. This paper uses the China’s income tax sharing policy to examine the impact of fiscal centralization on firms’ sustainable export innovation behavior. We find that this tax reform has significantly inhibited the increase of the export value-added rate of firms, and has an increasing trend with the share ratio between the Central Government and the local government. Moreover, this effect mainly comes from the crowding-out effect of imported intermediate goods on domestic intermediate goods. The tests show the above conclusions are consistent with the general logic of local governments. When they face greater downward fiscal pressure, they will further pass the tax burden on local firms and force firms to promote their export performance to expand the tax base. This short-sighted behavior of replacing “quality improvement” with “quantity increase” is an important factor that affects firms’ sustainable export innovation behavior and the climb in the global value chain.